Species, Spatial-Temporal Distribution, and Contamination Assessment of Trace Metals in Typical Mariculture Area of North China - Pan, Dawei; Ding, Xiaoyan; Han, Haitao; Zhang, Shenghui; Wang, Chenchen (Frontiers in Marine Science, 2020)
The species, spatial-temporal distribution, sources, correlations with physiochemical factors, and the contamination of trace metals (Cu, Pb, Cd, and Zn) were investigated in a typical mariculture area of North China. The concentrations of three species of trace metals, including total dissolved, dissolved reactive, and dissolved inert, were obtained. The total dissolved concentrations of Cu, Pb, Cd, and Zn ranged within 1.75-8.08, 0.43-2.75, 0.07-0.29, and 2.58-30.28 μg/L, respectively. These ranges were measured over five months (March, May, July, September, and November) and their concentrations decreased in the following order: Zn > Cu > Pb > Cd. The concentrations of Cu, Pb, Cd, and Zn decreased from nearshore to offshore, showing a distinctly regional variation. All concentrations of trace metals over the whole mariculture area were lower than the grade-II seawater quality standard of China. The relationships between trace metals with micronutrient metal (Fe) and other environmental factors (i.e., temperature, chlorophyll a, salinity, dissolved oxygen, and conductivity) were studied in detail. Discharged industrial and aquaculture effluents, uptake by organisms, and atmospheric deposition resources were found to be possible sources of trace metals in the studied area. Sea current and physicochemical parameters were factors that possibly influenced the spatial-temporal distribution of trace metals.